Resolution enrichment of side scan sonar image using wavelet based interpolation methods - Kumudham, R; Tarun, S; Avinash, R; Rajendran, V (International Journal of Engineering and Technology, 2018)
The resolution of the side scan sonar image which is used to detect on seabed such as mines, ship wrecks, etc is low. This paper helps to utilizes image processing techniques to enhance the resolution and thereby it makes detection and classification of underwater objects accurately. The proposed methods discussed in this paper are Discrete wavelet transform and stationary wavelet transform for enhancing the resolution.Â Â